Efektivitas Penggunaan Iklan Instagram sebagai Media Promosi UMKM - Aun Ramlah Maharani; Ponirin Ponirin; Ira Nuriya Santi; Rian Risendy (Jurnal Kajian dan Penelitian Umum, 2024)
Instagram, also known as IG, is a social media company founded in 2010 by Kevin Systrom. Instagram is a social network that offers video and photo sharing services, and Instagram itself is one of the most widely used social networks in the world. In 2017, Instagram released a new feature to make advertising easier, namely the Instagram Sponsored Feature. Many business people are starting to use the Instagram Sponsored feature as a digital advertising medium, following in the footsteps of Facebook Ads, entrepreneurs seem interested in Instagram Sponsored seeing the increasing development of Instagram users which certainly attracts entrepreneurs' interest in promoting their products through Instagram Sponsored. The research was conducted using a qualitative descriptive method with a case study of Snacky Plw. This research uses primary and secondary databases. The primary data used was obtained through direct observations in the field while running the business as well as information from internal parties involved. The results of the research are that effectiveness can be used in various activities, one of which is to see the success of a business based on promotions carried out by MSMEs. The promotions carried out by MSMEs in this era of information technology are very diverse because they can get the opportunity to use various social media to promote their products, one of which is the social media Instagram, which is very popular with the wider community and is used as a favorite social media for MSMEs to promote their products. With the existence of Instagram, MSME owners create various content with a variety of different themes, as well as creative and innovative as well as high resolution images and videos, thereby making consumers interested in the MSME products being sold. Seen from insight data, it shows an increase in the profile of visits which has increased by more than 50% compared to before using ads.